P31 The evolving role of cardiac MRI in the patient with connective tissue disease. (20th April 2020) - Benson, Rosalind; Waters, Lisa; Magapu, Pradeep; Sadik, Hala
Abstract: Background: An atypical presentation of a new diagnosis of undifferentiated CTD highlights the use of cardiac MRI in CTD. In comparison to echocardiogram it can better establish cardiac involvement in CTD which is associated with significant morbidity and mortality. Methods: A 49 year old previously well man was referred to rheumatology clinic with symptoms of inflammatory sounding arthralgia, new onset Raynauds, fatigue and 1 stone weight loss. In the interim he presented acutely with dyspnoea and chest pain and was found to be in atrial fibrillation. A chest X-ray was suggestive of pneumonitis and bibasal patchy consolidation. Despite antibiotics the AF persisted, and anticoagulation and rate control was initiated. He represented two weeks later with severe arthralgia, joint swelling and malaise. Bloods showed: CRP 283, ESR 87, lymphopenia but normal renal and liver function. He was pyrexial and tachycardic, but a septic screen was negative and he had limited response to antibiotic therapy. A CT Chest showed extensive lymphadenopathy, bilateral pleural effusions and an enhancing pericardial effusion suggestive of pericarditis, confirmed by echocardiogram. A provisional diagnosis of systemic inflammation secondary to an undifferentiated CTD was made and after initiation of oral prednisolone and colchicine he had significant improvement in symptoms. A repeat CT chest one month later has shown resolution of the mediastinal lymphadenopathy and interstitial changes. Cardiac MRI has confirmed likely infiltrative cardiomyopathy consistent with a connective tissue disease. His ANA is 1:2560 speckled/ nucleolar pattern, ENA negative, anti CCP 55 and Ra Latex 65, DsDNA and complements normal. ACE and ANCA negative and the formal diagnosis of an undifferentiated CTD has been made. Methotrexate was introduced causing resolution of symptoms by 6 months of treatment. Follow up imaging is planned. Results: Cardiac MRI (CMR) in CTD is a relatively new imaging modality. Increasingly we are recognising that patients can have abnormalities seen on CMR despite a normal echo. CMR has identified occult cardiac disease in patients with treatment naive CTD which is potentially reversible with immunosuppresion. We also know that despite serological normalisation and systemic improvement of symptoms cardiac involvement can be subclinical. CMR as a non-radiating and non-invasive imaging modality is ideally placed to assess response to treatment in those with CTD related cardiac involvement. Indications for CMR in CTD has been further delineated in guidance from the International consensus group of Cardiac MRI in CTD. Conclusion: In our patient identification of his new atrial arrhythmia prompted the instigation of cardiac investigations which culminated in CMR. Close working with cardiology colleagues and subsequent access to their tertiary MDT has meant we have better characterised our patient's cardiac involvement translating to rapid immunosuppression and planned treatment monitoring with further CMR. Disclosures: R. Benson None. L. Waters None. P. Magapu None. H. Sadik None.